SOSIALISASI PEMBUATAN CILOK DAN PANGSIT BAKSO UNTUK MENINGKATKAN PENDAPATAN EKONOMI MASYARAKAT PADA KELOMPOK PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) DAN MASYARAKAT DUSUN BERAMBANG DESA BATU PUTIH KABUPATEN LOMBOK BARAT - Dewi Rispawati; Vidya Yanti Utami; Nasruddin, Nasruddin; Siti Hidayatul Juma’ah; Johan Mashuri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
This Community Service is entitled Socialization of Making Cilok and Meatball Dumplings to Increase Community Income in the Community Empowerment and Welfare Group (PKK) and Berambang Hamlet Community, Batu Putih Village, West Lombok Regency, which aims to increase community income in Berambang Hamlet. The method used in this Community Service activity is implemented in 4 (four) activity stages, namely: 1) Preparation, 2) Socialization, 3) Implementation of Activities, and 4) Monitoring and Evaluation. The results of the activity show that the people in Berambang Hamlet, Batu Putih Village, West Lombok Regency are very enthusiastic and have understood how to make Cilok and Meatball Dumplings which has been socialized, so that they can be practiced directly and can enjoy the results of making Cilok and Meatball Dumplings by the people of Berambang Hamlet. Making Cilok and Meatball Dumplings can increase people's income because they have selling value and community members who are entrepreneurs can increase their income by selling Cilok and Meatball Dumplings which are very popular with the people of Berambang Hamlet and its surroundings. Cilok and Meatball Dumplings are also popular with children, teenagers and even all groups in the community of Berambang Hamlet, Batu Putih Village, West Lombok Regency